Four decades of Canadian earnings inequality and dynamics across workers and firms - Audra J. Bowlus; Émilien Gouin Bonenfant; Huju Liu; Lance Lochner; Youngmin Park (Quantitative Economics, 2022)
This paper studies the evolution of individual earnings inequality and dynamics in Canada from 1983 to 2016 using tax files and administrative records. Linking individual tax filers to their employers (and rich administrative records on firms) beginning in 2001, it also documents the relationship between the earnings dynamics of workers and the size and growth of their employers. It highlights three main patterns over this period: First, with a few exceptions (sharp increase in top 1% and declining gender gap), Canada has experienced relatively modest changes in overall earnings inequality, volatility, and mobility between 1983 and 2016. Second, earnings inequality and the distribution of earnings growth vary substantially over the business cycle. Third, the earnings dynamics of individuals are strongly related to the size and employment growth of their employers.
Keywords: E24; J24; J31; J62; L25; 330; Earnings inequality; earnings dynamics; firm dynamics